DETERMINATION OF STRATEGIES TO IMPROVE EMPLOYEE PERFORMANCE IN. FINANCE USING SMS METHODS AHP (ANALYTICAL HIERARCY PROCESS) - Antoni Yohanes (Jurnal Ilmiah Dinamika Teknik, 2011)
Performance is a thing that is individualized, as each employee has a different ability levels vary for doing his job. The management company can measure the performance of employees based on the performance of each employee. Performance is an action, not an event. Performance of the action itself consists of many components and is not a result that can be seen at the time as well. Strategy is an integrated, comprehensive and integrated corporate strategy excellence linking environmental challenges that are designed to ensure that corporate objectives can be achieved through proper execution by the company. Analytical Hierarchy Process (AHP) is a method of decision-making on the issue of prioritization of choice alternatives. Using AHP begins by making the hierarchical structure of the problem to study. Pairwise comparison matrices are used to establish relationships within the structure. In the pairwise comparison matrix will be sought from the weight of each criterion in the AHP strategies to improve employee performance with a range of alternatives can be seen that the highest priority to improving the quality of 0.3871. followed by improvement of infrastructure and welfare weighing 0.3610 and 0.2519.   Keywords: Performance, Strategy, AHP